2022
DOI: 10.3390/cryst12020302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fineness and Heat Treatment on the Pozzolanic Activity of Natural Volcanic Ash for Its Utilization as Supplementary Cementitious Materials

Abstract: The aim of this study was to investigate the influence of fineness and heat-treatment on the pozzolanic and engineering properties of volcanic ash. To this end, two different fineness levels of volcanic ash, ultra-fine (VAF) and fine (VA), without and after heat treatment at different temperatures (VA550, VA650, and VA750), were partially substituted for cement. In addition to the control (100% cement), five binary mortar mixes, each containing 20% of the different types of volcanic ash (VAF and VA; heat-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 48 publications
1
9
1
Order By: Relevance
“…This finding was more evident in mortars containing 5% of silica fume. Through the pozzolanic reactions, coarse silica fume combined with calcium hydroxide, providing a denser microstructure and rendering free lime unavailable for acid or sulphates attacks [31]. Kwon et al reported that specimens incorporating silica fume showed a denser microstructure, which is explained by the pore filling effect [32].…”
Section: Microstrural Characteristicsmentioning
confidence: 99%
“…This finding was more evident in mortars containing 5% of silica fume. Through the pozzolanic reactions, coarse silica fume combined with calcium hydroxide, providing a denser microstructure and rendering free lime unavailable for acid or sulphates attacks [31]. Kwon et al reported that specimens incorporating silica fume showed a denser microstructure, which is explained by the pore filling effect [32].…”
Section: Microstrural Characteristicsmentioning
confidence: 99%
“…The XRD analysis results of red and black scoria after thermal treatment showed differences between the crystal structure phases and minerals of the two scoriae. As the thermal treatment temperature increased, the intensity of the peaks in red scoria decreased, whereas the peaks in black scoria presented new phases of minerals and a decrease in the amount of amorphous phase (hump), possibly causing the degradation of mechanical properties [ 4 ]. Nevertheless, owing to the complexity of the chemical compositions of volcanic scoria, the spectra of likely minerals expanded with thermal treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Environmental pollution has been exacerbated by increased CO 2 levels in the air, particularly from the manufacture of building materials such as cement, thus contributing to climate change and global warming [ [1] , [2] , [3] , [4] ]. Moreover, the growing demand for building insulation to save energy consumption has necessitated the identification of environment friendly and cost-effective substitutes for cement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various types of industries, the cement sector is one of the largest contributors to CO 2 , estimated at around 8% of total anthropogenic greenhouse gas (GHG) emissions [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. One of the ways to reduce this impact is to reduce cement consumption by partially replacing it with supplementary cementitious materials (SCMs), which can be by-products from industry or natural pozzolans (NP), such as fly ash (FA), ground granulated blast furnace slag (GGBS), silica fume (SF), metakaolin (MK), limestone (L), fine glass powder (GP), rice husk ash (RHA), and volcanic tuffs (natural pozzolans) [ 5 , 6 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. These latter SCMs include both pozzolanic tuffs and those from the extraction of quarry aggregates.…”
Section: Introductionmentioning
confidence: 99%